Сomparative Analysis of the Long-Term Results of Diabetic Macular Edema and Epiretinal Membrane Surgical Treatment - M. M. Bikbov; R. M. Zainullin; T. R. Gilmanshin; T. A. Khalimov (Oftalʹmologiâ, 2019)
The purpose of the study — to conduct a comparative analysis of structural and functional indicators of the central zone of the retina in patients with diabetic macular edema and epiretinal membrane in the remote period after surgical treatment. Patients and Methods. We examined 97 patients with diabetic macular edema in combination with the epiretinal membrane aged 53 to 68 years (mean age 61 ± 5.4 years). All patients underwent vitrectomy with an internal limiting membrane peeling (ILM). Patients were divided into 3 groups depending on the intravitreal use of an angiogenesis inhibitor. The analysis of the remote anatomical and functional results of patients of different groups during 1 year of observation was carried out. Results. In patients after treatment using the proposed technique, the central retinal thickness was reduced by 16.19 % (p = 0.031) compared with monotherapy and by 11.51 % (p = 0.039) compared with a phased treatment method. Visual acuity significantly increased in the treatment group by the single-step method by 1.53 times (p = 0.024) compared with the group where only vitrectomy was performed, and also 1.44 times (p = 0.029) compared with the delayed administration of angiogenesis inhibitor in avital eye. Patients in all groups have showed an improvement in central photosensitivity 1 month after surgery, followed by a slight decrease in performance. However, by 12 months, the level of central photosensitivity in group 2 was significantly higher than in other groups (p < 0.05). A comparative analysis of the spatial distribution of macular pigment has showed that, along with the development of the pathological process, macular pigments were dispersed in the retinal tissue. On the background of treatment, their concentration was normalized in the central zone of the retina, without increasing the quantitative composition. Conclusion Analysis of the morphofunctional parameters of the retina central section in patients with diabetic macular edema and epiretinal membrane in the dynamics of treatment with various techniques led to the creation of an algorithm for managing patients. It allows to achieve high clinical and functional results in an overwhelming percentage of cases and, thereby, significantly improve medical and social rehabilitation, and also the quality of life of this contingent.